2019
DOI: 10.1055/s-0039-1687889
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnosis of Inherited Coagulation and Bleeding Disorders

Abstract: Diagnosis of inherited bleeding disorders (IBDs) remains challenging, especially in the case of inherited platelet disorders, due to the heterogeneity of the clinical and laboratory phenotype, the limited specificity of platelet function tests, and the large number of potential culprit genes. Unraveling the underlying molecular defect provides the definitive diagnosis of IBDs, facilitating prognosis and clinical care, which are especially important for severe clinical syndromes and those that may be associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 92 publications
0
57
0
1
Order By: Relevance
“…32 The implementation of HTS platforms in routine clinical practice has enabled the identification of RUNX1 variants in some patients with suspected IPD who lack a specific phenotype. 7,10 However, the definitive diagnosis of FPD/AML in these patients requires an accurate assessment of the pathogenicity of their RUNX1 variants. 16,17 In this context, the p.Leu56Ser alteration in RUNX1 has been found in some patients with clinical and laboratory suspicion of FPD/AML, but is also a relatively frequent variant in the general population (up to 0.017 in the European non-Finnish population, according to GnomAD).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 The implementation of HTS platforms in routine clinical practice has enabled the identification of RUNX1 variants in some patients with suspected IPD who lack a specific phenotype. 7,10 However, the definitive diagnosis of FPD/AML in these patients requires an accurate assessment of the pathogenicity of their RUNX1 variants. 16,17 In this context, the p.Leu56Ser alteration in RUNX1 has been found in some patients with clinical and laboratory suspicion of FPD/AML, but is also a relatively frequent variant in the general population (up to 0.017 in the European non-Finnish population, according to GnomAD).…”
Section: Discussionmentioning
confidence: 99%
“…6 As in most inherited platelet disorders (IPDs), RUNX1related disorder (RUNX1-RD) lacks a specific clinical and laboratory phenotype, which makes genetic diagnosis essential. 7 The introduction of high-throughput sequencing (HTS) techniques into mainstream genetic diagnostic practice for IPDs has shown that molecular variations in TFs are far more frequent than previously believed. [8][9][10] To date, more than 130 families with RUNX1 variants have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly reported subtypes are HPS-1, HPS-3, and HPS-4. The HPS1 gene was first screened by SS in patients with severe phenotypes and in Puerto Rican patients [4,18], while founder mutations in HPS3 were analyzed in patients with mild phenotypes and in Ashkenazi Jewish patients [2,19]. In addition, the prevalence of HPS-4, one of the severe forms of the disease, is relatively high in different populations, such as Japanese, or inhabitants of Mediterranean regions, among others [1,4,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Public databases and in silico platforms provides extensive information. Finally, variants were classified according to the American College of Medical Genetics and Genomics recommendations [9,[15][16][17][18]. The causative genetic variants were also confirmed in the patients and screened in the available family members by Sanger sequencing (SS).…”
Section: Methodsmentioning
confidence: 99%
“…The spread of next-generation sequencing (NGS) greatly contributed to the unraveling of the genetic basis of several forms of IPD, and thus immediately became a significant diagnostic tool in the field. Using a small amount of blood with minor risk of pre-analytical artifacts, it can provide patients with a highly accurate diagnosis [4][5][6][7][66][67][68][69][70][71][72]. As it becomes cheaper to perform, it is not inconceivable that NGS could become the standard above other diagnostic techniques.…”
Section: Current Diagnostic Tools For Ipdsmentioning
confidence: 99%